Cyclic imide resin composition, liquid adhesive, film, prepreg, copper-clad laminate, and printed wiring board

By using a specific cyclic imide resin composition, the problems of insufficient adhesion and thermal resistance performance of existing resins in high-frequency printed circuit board applications are solved, and the effects of low phase electrical constant, low loss arc and high glass transition temperature are achieved.

JP7665271B2Active Publication Date: 2025-04-21SHIN ETSU CHEMICAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022012543
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-01-31
Publication Date
2025-04-21
Estimated Expiration
2042-01-31

AI Technical Summary

Technical Problem

The existing male imide resins have a need for low adhesion and long-term baking for high temperatures in high-frequency printed circuit board applications, resulting in low production efficiency and insufficient thermal resistance performance of improved resins at low temperatures and short-term baking.

Method used

A cyclic imide resin composition is used, which comprises a specific cyclic imide compound, a two-component with a specific dipole moment and a catalyst to improve the adhesion and thermal resistance of the resin.

Benefits of technology

The low phase electrical constant, low loss arc and high glass transition temperature of the cyclic imide resin are achieved, and the adhesion and thermal resistance of the resin are improved, making it suitable for the manufacturing of high-frequency printed circuit boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665271000001
    Figure 0007665271000001
  • Figure 0007665271000002
    Figure 0007665271000002
  • Figure 0007665271000003
    Figure 0007665271000003
Patent Text Reader

Abstract

To provide a cyclic imide resin composition which gives a cured product having a low relative dielectric constant, a low dielectric loss tangent, high adhesive force and a high glass transition point.SOLUTION: A cyclic imide resin composition contains the following components (a) to (c). (a) Cyclic imide compound represented by the following formula (1). In the formula (1), A independently represents a tetravalent organic group including a cyclic structure, B independently represents a divalent hydrocarbon group, X represents a hydrogen atom or a methyl group, and m represents 1 to 1,000, (b) a compound having a molecular weight of less than 2,000 and at least two alkenyl groups in one molecule, in which (b1) 1-50 pts.mass of a compound having a dipolar moment calculated by Gaussian 16 of less than 1.2 DeBye, with respect to 100 pts.mass of the component (a), and (b2) 10 pts.mass or less of a compound having a dipolar moment calculated by Gaussian 16 of 1.2 DeBye or more, with respect to 100 pts.mass of the component (a), and (c) a curing catalyst.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cyclic imide resin composition and the like. [Background technology]

[0002] In recent years, the speed and capacity of signals used in electronic devices, such as mobile communication devices typified by mobile phones, their base station equipment, network infrastructure devices such as servers and routers, and large computers, are increasing year by year. Accordingly, high frequency bands such as the 20 GHz range are used for the printed wiring boards mounted on these electronic devices, and the properties required of printed wiring board materials are becoming increasingly high, such as low dielectric constant, low dielectric loss tangent, low coefficient of thermal expansion, high heat resistance, and low water absorption.

[0003] Materials that may satisfy these characteristics include modified polyphenylene ether resins, maleimide resins, epoxy resins, etc. (Patent Documents 1 to 3) Among these, maleimide resins have a low dielectric constant, a low dielectric loss tangent, and high heat resistance, and therefore are used as materials for high-frequency printed wiring boards (Patent Documents 4 and 5).

[0004] However, typical maleimide resins have low adhesive strength and require long-term curing at high temperatures to produce sufficient properties, making them unsuitable for mass production of products using maleimide resins. Furthermore, Patent Document 6 discloses a resin composition containing a maleimide compound containing at least one of an alkyl group having 5 or more carbon atoms and an alkylene group having 5 or more carbon atoms. Although this resin composition can be cured at a relatively low temperature in a short time, it has problems in that the adhesive strength is insufficient, and the cured product has a low glass transition point and poor heat resistance. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2019-1965 A [Patent Document 2] JP 2018-28044 A [Patent Document 3] JP 2018-44065 A [Patent Document 4] International Publication No. 2016-114286 [Patent Document 5] JP 2020-45446 A [Patent Document 6] Patent Publication No. 2021-11587 Summary of the Invention [Problem to be solved by the invention]

[0006] Accordingly, an object of the present invention is to provide a cyclic imide resin composition which gives a cured product having a low dielectric constant, a low dielectric tangent, high adhesive strength and, at the same time, a high glass transition point. [Means for solving the problem]

[0007] As a result of intensive research aimed at solving the above problems, the present inventors have found that the following cyclic imide resin composition can achieve the above object, and have completed the present invention. That is, the present invention provides the following cyclic imide resin composition, etc.

[0008] [1] A cyclic imide resin composition comprising the following components (a), (b) and (c): (a) A cyclic imide compound represented by the following formula (1) having a weight average molecular weight of 2,000 to 1,000,000: [ka] (In formula (1), A independently represents a tetravalent organic group containing a cyclic structure. B independently represents a divalent hydrocarbon group having 6 or more carbon atoms which may contain a heteroatom. X represents a hydrogen atom or a methyl group. m represents an integer of 1 to 1000.) (b) A compound having a molecular weight of less than 2,000 and having at least two groups selected from an alkenyl group, a maleimide group, a (meth)acrylic group, an epoxy group, and a cyanate group in each molecule, (b1) A compound having a dipole moment of less than 1.2 DeBye calculated by Gaussian 16: 1 to 50 parts by mass per 100 parts by mass of component (a) (b2) A compound having a dipole moment of 1.2 DeBye or more calculated by Gaussian 16 (10 parts by mass or less per 100 parts by mass of the (a) component) (c) Curing catalyst [2] The cyclic imide resin composition according to [1], wherein the organic group represented by A in the formula (1) is any one of tetravalent organic groups represented by the following structural formulas: [ka] (The bond not bonded to a substituent in the above structural formula is bonded to the carbonyl carbon that forms a cyclic imide structure in formula (1).) [3] The cyclic imide resin composition according to [1], wherein the cyclic imide compound of the component (a) is a cyclic imide compound represented by the following formula (2): [ka] (In formula (2), A independently represents a tetravalent organic group containing a cyclic structure. B 1 are independently an alkylene group having 6 to 60 carbon atoms which may contain a heteroatom or a divalent hydrocarbon group derived from a dimer acid skeleton. 2 are independently an arylene group having 6 to 30 carbon atoms which may contain a heteroatom. X is a hydrogen atom or a methyl group. W is B 1 Or B 2 m 1 is 0 to 500, m 2 is between 1 and 500.) [4] B in formula (2) 1The cyclic imide resin composition according to [3], wherein the alkylene group having 6 to 60 carbon atoms and which may contain a heteroatom is selected from groups represented by the following structural formulas and divalent hydrocarbon groups derived from a dimer acid skeleton. [ka] (R 1 Each represents independently a hydrogen atom or a linear or branched alkyl group having 1 to 20 carbon atoms. 1 and p 2 are each a number equal to or greater than 5 and may be the same or different, and p 3 and p 4 are each a number equal to or greater than 0 and may be the same or different, and p 5 is a number from 6 to 60. The bond to which no substituent is bonded in the above structural formula is bonded to the nitrogen atom that forms a cyclic imide structure in formula (2). [5] B in formula (2) 2 The cyclic imide resin composition according to [3] or [4], wherein the arylene group having 6 to 30 carbon atoms and optionally containing a heteroatom, represented by the following structural formula, is any of the groups represented by the following structural formulas: [ka] (R 2 are each independently a hydrogen atom, a halogen atom, or an alkyl group having 1 to 6 carbon atoms; R 3 are each independently a hydrogen atom, a halogen atom, a methyl group, or a trifluoromethyl group, and Z is an oxygen atom, a sulfur atom, or a methylene group. The bond to which no substituent is bonded in the above structural formula is bonded to the nitrogen atom that forms a cyclic imide structure in formula (2). [6] The cyclic imide compound of the component (a) is represented by m in the formula (2). 1 The cyclic imide resin composition according to any one of [3] to [5], wherein the cyclic imide compound is a cyclic imide compound having a moiety of 0. [7] A liquid adhesive comprising the cyclic imide resin composition according to any one of [1] to [6]. [8] A film comprising the cyclic imide resin composition according to any one of [1] to [6]. [9] A prepreg comprising the cyclic imide resin composition according to any one of [1] to [6].

[10] A copper-clad laminate comprising the prepreg according to [9].

[11] A printed wiring board comprising the copper-clad laminate according to

[10] . Effect of the Invention

[0009] The cyclic imide resin composition of the present invention provides a cured product having a low dielectric constant, a low dielectric tangent, and a high adhesive strength, while having a high glass transition point. Therefore, the cyclic imide resin composition of the present invention is useful for applications such as adhesives, prepregs, copper-clad laminates, printed wiring boards, base films for flexible printed wiring boards, coverlay films, adhesives for coverlay films, heat dissipation adhesives, electromagnetic wave shields, and semiconductor encapsulants. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The cyclic imide resin composition of the present invention will be described in detail below.

[0011] [(a) A cyclic imide compound represented by the following formula (1) having a weight average molecular weight of 2,000 to 1,000,000] The cyclic imide compound of component (a) is the main component of the cyclic imide resin composition of the present invention, and is represented by the following formula (1): By including component (a) in the cyclic imide resin composition of the present invention, it is possible to achieve a low relative dielectric constant, a low dielectric loss tangent, and high strength for the cured product of the resin composition. [ka] In formula (1), A independently represents a tetravalent organic group containing a cyclic structure. B independently represents a divalent hydrocarbon group having 6 or more carbon atoms which may contain a heteroatom. X represents a hydrogen atom or a methyl group. m is 1 to 1000.

[0012] Here, the organic groups represented by A in formula (1) are independently tetravalent organic groups containing a cyclic structure, and are particularly preferably any of the tetravalent organic groups represented by the following structural formulas. [ka] The bond not bonded to a substituent in the above structural formula is bonded to the carbonyl carbon that forms a cyclic imide structure in formula (1).

[0013] Furthermore, B in formula (1) is independently a divalent hydrocarbon group having 6 or more carbon atoms which may contain a heteroatom, and is preferably a divalent hydrocarbon group having 6 to 60 carbon atoms which may contain a heteroatom. B is preferably an alkylene group having 6 to 60 carbon atoms which may contain a heteroatom, a divalent hydrocarbon group derived from a dimer acid skeleton, or an arylene group having 6 to 30 carbon atoms which may contain a heteroatom.

[0014] The alkylene group having 6 to 60 carbon atoms which may contain a heteroatom is, for example, B 1 As the substituent, the same groups as those exemplified above can be mentioned, and more specifically, any of the groups represented by the following structural formulas can be mentioned as being particularly preferred. [ka] The bond not bonded to a substituent in the above structural formula is bonded to the nitrogen atom forming a cyclic imide structure in formula (1).

[0015] In the above formula, R 1are each independently a hydrogen atom or a linear or branched alkyl group having 1 to 20 carbon atoms, preferably a hydrogen atom or a linear or branched alkyl group having 1 to 10 carbon atoms, and more preferably a hydrogen atom or a linear alkyl group having 1 to 10 carbon atoms. In the above formula, p 1 and p 2 are each a number of 5 or more, preferably a number of 5 to 12, more preferably a number of 6 to 10, and may be the same or different. p 3 and p 4 is a number of 0 or more, preferably a number of 0 to 4, more preferably a number of 0 to 2, and may be the same or different. In the above formula, p 5 is a number from 6 to 60, preferably a number from 6 to 40, and more preferably a number from 6 to 20.

[0016] In addition, the arylene group having 6 to 30 carbon atoms which may contain a heteroatom includes B 2 As the substituent, the same groups as those exemplified above can be mentioned, and more specifically, any of the groups represented by the following structural formulas can be mentioned as being particularly preferred. [ka] The bond not bonded to a substituent in the above structural formula is bonded to the nitrogen atom forming a cyclic imide structure in formula (1).

[0017] In the above formula, R 2 are each independently a hydrogen atom, a halogen atom or an alkyl group having 1 to 6 carbon atoms, preferably a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and more preferably a hydrogen atom, a methyl group or an ethyl group. In the above formula, R 3 are each independently a hydrogen atom, a halogen atom, a methyl group, or a trifluoromethyl group, and are preferably a hydrogen atom, a methyl group, or a trifluoromethyl group. In the above formula, Z is an oxygen atom, a sulfur atom or a methylene group, and is preferably an oxygen atom or a sulfur atom.

[0018] In formula (1), X is a hydrogen atom or a methyl group, and is preferably a hydrogen atom.

[0019] In the formula (1), m is a number from 1 to 1,000, and preferably a number from 1 to 900.

[0020] As the cyclic imide compound represented by formula (1), a cyclic imide compound represented by the following formula (2) is more preferable. [ka] In formula (2), A independently represents a tetravalent organic group containing a cyclic structure. 1 are independently an alkylene group having 6 to 60 carbon atoms which may contain a heteroatom or a divalent hydrocarbon group derived from a dimer acid skeleton. 2 are independently an arylene group having 6 to 30 carbon atoms which may contain a heteroatom. X is a hydrogen atom or a methyl group. W is B 1 Or B 2 m 1 is 0 to 500, m 2 is between 1 and 500.

[0021] Examples of the tetravalent organic group containing a cyclic structure represented by A in formula (2) include the same groups as those exemplified for A in formula (1). [ka] The bond not bonded to a substituent in the above structural formula is bonded to the carbonyl carbon that forms a cyclic imide structure in formula (2).

[0022] B in formula (2) 1 The alkylene group having 6 to 60 carbon atoms and optionally containing a heteroatom, represented by the formula: is preferably an alkylene group having 8 to 50 carbon atoms and optionally containing a heteroatom, and more preferably an alkylene group having 8 to 40 carbon atoms. 1The alkylene group having 6 to 60 carbon atoms and optionally containing a heteroatom, represented by the following formula (I) may have any of a linear, branched, or cyclic structure, or may be a group combining a plurality of these structures. 1 Particularly preferred examples of the alkylene group having 6 to 60 carbon atoms and optionally containing a heteroatom, represented by the following structural formula, include any of the groups represented by the following structural formulas or a divalent hydrocarbon group derived from a dimer acid skeleton. [ka] The bond not bonded to a substituent in the above structural formula is bonded to the nitrogen atom forming a cyclic imide structure in formula (2).

[0023] In the above formula, R 1 are each independently a hydrogen atom or a linear or branched alkyl group having 1 to 20 carbon atoms, preferably a hydrogen atom or a linear or branched alkyl group having 1 to 10 carbon atoms, and more preferably a hydrogen atom or a linear alkyl group having 1 to 10 carbon atoms. In the above formula, p 1 and p 2 are each a number of 5 or more, preferably a number of 5 to 12, more preferably a number of 6 to 10, and may be the same or different. p 3 and p 4 is a number of 0 or more, preferably a number of 0 to 4, more preferably a number of 0 to 2, and may be the same or different. In the above formula, p 5 is a number from 6 to 60, preferably a number from 6 to 40, and more preferably a number from 6 to 20.

[0024] B in formula (2) 1Dimer acid is a liquid dibasic acid that is produced by dimerizing unsaturated fatty acids with 18 carbon atoms, such as vegetable oils, and is composed mainly of dicarboxylic acids with 36 carbon atoms. Dimer acids do not have a single skeleton, but rather have multiple structures, and there are several types of isomers. Representative dimer acids are classified as linear (a), monocyclic (b), aromatic (c), and polycyclic (d). In this specification, the dimer acid skeleton refers to a group derived from a dimer diamine having a structure in which the carboxy group of such a dimer acid is substituted with a primary aminomethyl group. That is, B 1 When is a divalent hydrocarbon group derived from a dimer acid skeleton, examples thereof include, but are not limited to, groups in which the two carboxyl groups in each of the dimer acids shown in (a) to (d) below are substituted with methylene groups. Furthermore, from the viewpoint of heat resistance and reliability of the cured product, it is more preferable that the divalent hydrocarbon group derived from the dimer acid skeleton has a structure in which the carbon-carbon double bonds in the hydrocarbon group derived from the dimer acid skeleton are reduced by a hydrogenation reaction. [ka] As described above, the dimer acid skeleton has a plurality of structures, and therefore, in this specification, the divalent hydrocarbon group derived from the dimer acid skeleton is referred to as the average structure, i.e., -C 36 H 70 It may be written as -.

[0025] In formula (2), B 2 The arylene group having 6 to 30 carbon atoms which may contain a heteroatom, represented by the formula: is preferably an arylene group having 10 to 30 carbon atoms which may contain a heteroatom, and more preferably an arylene group having 20 to 30 carbon atoms. 2 The arylene group having 6 to 30 carbon atoms and optionally containing a heteroatom, represented by the following formula (I) is a divalent group obtained by removing two hydrogen atoms bonded to carbon atoms constituting an aromatic ring from an aromatic hydrocarbon. The aromatic hydrocarbon includes the following compounds: Monocyclic or polycyclic aromatic hydrocarbons Compounds in which two or more independent monocyclic or polycyclic aromatic hydrocarbons are bonded via a single bond or a divalent organic group More specifically, B 2 As the arylene group having 6 to 30 carbon atoms which may contain a heteroatom and is represented by the following formula, groups represented by any of the following structural formulas can be mentioned as being preferable.

[0026] [ka] The bond not bonded to a substituent in the above structural formula is bonded to the nitrogen atom forming a cyclic imide structure in formula (2).

[0027] In the above formula, R 2 are each independently a hydrogen atom, a halogen atom or an alkyl group having 1 to 6 carbon atoms, preferably a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and more preferably a hydrogen atom, a methyl group or an ethyl group. In the above formula, R 3 are each independently a hydrogen atom, a halogen atom, a methyl group, or a trifluoromethyl group, and are preferably a hydrogen atom, a methyl group, or a trifluoromethyl group. In the above formula, Z is an oxygen atom, a sulfur atom or a methylene group, and is preferably an oxygen atom or a sulfur atom.

[0028] In formula (2), X is a hydrogen atom or a methyl group, and is preferably a hydrogen atom.

[0029] In formula (2), m 1 is 0 to 500, preferably 0 to 300. In formula (2), m 2 is a number from 1 to 500, preferably 1 to 300.

[0030] In the above formula (2), m 1 When R 2 is 0, the cyclic imide compound of the component (a) is represented by the following formula (2-1). [ka] (In formula (2-1), A, B 2 , X and m 2 are the same as in equation (2).) It is particularly preferred to use a cyclic imide compound represented by formula (2-1) as the cyclic imide compound of component (a) because this increases the glass transition temperature of the cured product of the resin composition.

[0031] The weight average molecular weight (Mw) of the cyclic imide compound of component (a) is 2,000 to 1,000,000, preferably 2,500 to 500,000, more preferably 3,000 to 300,000, and even more preferably 3,500 to 100,000. If the weight average molecular weight is less than 2,000, the strength of the cured product of the cyclic imide resin composition will be low, and if the weight average molecular weight is more than 1,000,000, the reactivity of the terminal cyclic imide groups will be low, making it difficult to sufficiently cure the composition.

[0032] The weight average molecular weight (Mw) referred to in this specification refers to the weight average molecular weight measured by GPC under the following conditions using polystyrene as the standard. [GPC measurement conditions] Developing solvent: Tetrahydrofuran Flow rate: 0.6mL / min Column: TSK Guardcolumn SuperH-L TSKgel SuperH4000(6.0mmI.D.×15cm×1) TSKgel SuperH3000(6.0mmI.D.×15cm×1) TSKgel SuperH2000(6.0mmI.D.×15cm×2) (All manufactured by Tosoh Corporation) Column temperature: 40℃ Sample injection volume: 20 μL (sample concentration: 0.5% by mass in tetrahydrofuran solution) Detector: Differential refractometer (RI)

[0033] The method for producing the cyclic imide compound (a) (e.g., maleimide compound, citraconic imide compound, etc.) is not particularly limited. For example, the compound may be produced by reacting an acid anhydride with a diamine to synthesize an amine-terminated compound, and then reacting the amine-terminated compound with an excess of maleic anhydride or citraconic anhydride. Examples of the acid anhydride include pyromellitic anhydride, maleic anhydride, succinic anhydride, 4,4'-carbonyldiphthalic anhydride, 4,4'-diphthalic anhydride, 4,4'-sulfonyldiphthalic anhydride, 4,4'-oxydiphthalic anhydride, 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride, etc. These acid anhydrides may be used alone or in combination of two or more depending on the purpose, application, etc. From the viewpoint of the electrical properties of the cyclic imide compound, the acid anhydride is preferably pyromellitic anhydride, 4,4'-oxydiphthalic anhydride, or 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride.

[0034] Examples of diamines include 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 4,4'-diamino-3,3'-dimethyldiphenylmethane, 4,4'-diamino-3,3'-diethyldiphenylmethane, 4,4'-diaminodiphenyl ether, 4,4'-diamino-3,3',5,5'-tetraethyldiphenylmethane, tetramethyl-1,3-bis(3-aminopropyl)disiloxane, bis[4-(4-aminophenoxy)phenyl]sulfone, 4,4'-diamin Examples of the diamine include aminodiphenylmethane, 1,3-bis(4-aminophenoxy)benzene, 1,12-diaminododecane, 1,10-diaminodecane, dimer diamine, octyldiamine, 1,3-di(aminomethyl)cyclohexane, 1-amino-4-(aminomethyl)cyclohexane, 1,3-diaminoadamantane, isophoronediamine, 2,2,4-trimethylhexane-1,6-diamine, 2,4,4-trimethylhexane-1,6-diamine, 2-methylpentyldiamine, etc. Depending on the purpose, application, etc., one type of these diamines may be used alone, or two or more types may be used in combination. From the viewpoint of the electrical properties of the cyclic imide compound, the diamine is preferably 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 4,4'-diamino-3,3'-dimethyldiphenylmethane, 4,4'-diamino-3,3'-diethyldiphenylmethane, 4,4'-diaminodiphenyl ether, 4,4'-diamino-3,3',5,5'-tetraethyldiphenylmethane, dimer diamine, or isophoronediamine.

[0035] The cyclic imide compound of component (a) may be a commercially available product, such as BMI-1400, BMI-2500, BMI-3000, BMI-6000, or BMI-6100 (all manufactured by Designer Molecules Inc.). In the composition of the present invention, the amount of component (a) is preferably 40 to 98 parts by mass, more preferably 50 to 95 parts by mass, and even more preferably 60 to 90 parts by mass, per 100 parts by mass of the resin content. Note that the resin content here refers to the total amount of components (a) to (c), and includes the amount of component (d) and other additives, if present, but does not include the amount of inorganic fillers and organic fillers.

[0036] [(b) Component] Component (b) is a compound having a molecular weight of less than 2,000 and having at least two groups selected from an alkenyl group, a maleimide group, a (meth)acrylic group, an epoxy group, and a cyanate group in each molecule, and is the following component (b1) and component (b2) having mutually different dipole moments calculated with Gaussian 16:

[0037] The molecular weight of component (b) is less than 2,000, preferably 1,500 or less, and more preferably 1,000 or less. If the molecular weight of component (b) is 2,000 or more, it takes a long time to calculate the dipole moment using Gaussian 16, and the error in the calculation result becomes large, which is not preferable. In this specification, the molecular weight of component (b) is the value calculated from the molecular formula (chemical formula weight).

[0038] Component (b) has at least two groups selected from an alkenyl group, a maleimide group, a (meth)acrylic group, an epoxy group, and a cyanate group in one molecule. When component (b) has a (meth)acrylic group, the (meth)acrylic group is counted as one of the above groups, and the carbon-carbon double bond contained in the (meth)acrylic group is not counted as a duplicate in the number of alkenyl groups. Examples of the alkenyl group include a vinyl group, a 1-propenyl group, and an allyl group (2-propenyl group).

[0039] [(b1) A compound having a molecular weight of less than 2,000, at least two groups selected from an alkenyl group, a maleimide group, a (meth)acrylic group, an epoxy group, and a cyanate group in one molecule, and a dipole moment calculated by Gaussian 16 of less than 1.2 DeBye] By blending the compound of component (b1) in the cyclic imide resin composition of the present invention, the melt viscosity of the resin composition can be reduced, thereby improving the adhesion, and further the glass transition point of the cured resin composition can be increased. The (b1) component is preferably one having at least two groups selected from an alkenyl group and a maleimide group in one molecule, and more preferably one having at least three groups selected from an alkenyl group and a maleimide group in one molecule. When the resin composition contains such a (b1) component, it is preferable because the glass transition point of the cured resin composition can be increased.

[0040] Furthermore, the (b1) component, which is one of the (b) components, has a dipole moment calculated by Gaussian 16 of less than 1.2 DeBye, preferably 1.15 DeBye or less, and more preferably 1.1 DeBye or less. Within this range, the relative dielectric constant and dielectric loss tangent of the cured resin composition can be reduced, and further the melt viscosity of the resin composition can be reduced to enhance adhesion.

[0041] Here, Gaussian 16 is the name of quantum chemical calculation software. It is a device that calculates the dipole moment of a molecule using the density functional method, with wB97X as the exchange-correlation functional and 6-31+g** as the basis function.

[0042] Specific examples of compounds of component (b1) are given below, but are not limited to these. [ka] [ka] [ka] [ka]

[0043] The blending amount of the (b1) component is 1 to 50 parts by mass, more preferably 5 to 40 parts by mass, and even more preferably 10 to 30 parts by mass, per 100 parts by mass of the (a) component in the composition of the present invention. Within this range, the melt viscosity of the resin composition can be reduced without adversely affecting the physical properties of the resin composition.

[0044] [(b2) A compound having a molecular weight of less than 2,000, at least two groups selected from an alkenyl group, a maleimide group, a (meth)acrylic group, an epoxy group, and a cyanate group in one molecule, and a dipole moment calculated by Gaussian 16 of 1.2 DeBye or more] The cyclic imide resin composition of the present invention does not contain the component (b2), or if it contains the component (b2), the content in the composition is equal to or less than a certain amount as described below. Component (b2) is a compound having a molecular weight of less than 2,000, having at least two groups selected from an alkenyl group, a maleimide group, a (meth)acrylic group, an epoxy group, and a cyanate group in each molecule, and having a dipole moment calculated using Gaussian 16 of 1.2 DeBye or more. When the cyclic imide resin composition of the present invention contains the component (b2), the blending amount of the component (b2) is 10 parts by mass or less per 100 parts by mass of the component (a). Furthermore, when the cyclic imide resin composition of the present invention contains the (b2) component, the (b2) component is preferably 10 parts by mass or less per 100 parts by mass of the (a) component, and is an amount such that the ratio (amount of the (b2) component / (amount of the (a) component+amount of the (b1) component) is 0.1 or less, more preferably 0.08 or less, and even more preferably 0.05 or less. If the blending amount of the (b2) component is more than 10 parts by mass per 100 parts by mass of the (a) component, the relative dielectric constant and dielectric loss tangent of the cured resin composition will undesirably be too high.

[0045] Specific examples of compounds of component (b2) are given below, but are not limited to these. [ka]

[0046] [(c) Curing catalyst] Component (c) is a curing catalyst, and serves to cure the resin composition. The curing catalyst of component (c) is not particularly limited, but examples thereof include thermal radical polymerization initiators, thermal anionic polymerization initiators, and photopolymerization initiators.

[0047] Examples of the thermal radical polymerization initiator include methyl ethyl ketone peroxide, methylcyclohexanone peroxide, methylacetoacetate peroxide, acetylacetone peroxide, 1,1-bis(t-butylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(t-hexylperoxy)cyclohexane, 1,1-bis(t-hexylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane, 2,2-bis(4,4-di-t -butylperoxycyclohexyl)propane, 1,1-bis(t-butylperoxy)cyclododecane, n-butyl-4,4-bis(t-butylperoxy)valerate, 2,2-bis(t-butylperoxy)butane, 1,1-bis(t-butylperoxy)-2-methylcyclohexane, t-butyl hydroperoxide, p-menthane hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, t-hexyl hydroperoxide, dicumyl peroxide, 2,5-dimethyl 2,5-diethyl-2,5-bis(t-butylperoxy)hexane, α,α'-bis(t-butylperoxy)diisopropylbenzene, t-butylcumyl peroxide, di-t-butyl peroxide, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexyne-3, isobutyryl peroxide, 3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, lauroyl peroxide, cinnamic acid peroxide, m-toluoyl peroxide, benzoyl peroxide, diisopropyl Pyl peroxydicarbonate, bis(4-t-butylcyclohexyl) peroxydicarbonate, di-3-methoxybutyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, di-sec-butyl peroxydicarbonate, di(3-methyl-3-methoxybutyl) peroxydicarbonate, di(4-t-butylcyclohexyl) peroxydicarbonate, α,α'-bis(neodecanoylperoxy)diisopropylbenzene, cumyl peroxyneodecanoate, 1,1,3,3-Tetramethylbutylperoxyneodecanoate, 1-cyclohexyl-1-methylethylperoxyneodecanoate, t-hexylperoxyneodecanoate, t-butylperoxyneodecanoate, t-hexylperoxypivalate, t-butylperoxypivalate, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, 1-cyclohexyl-1-methylethylperoxy-2-ethylhexanoate, t-hexylperoxy peroxy-2-ethylhexanoate, t-butylperoxy-2-ethylhexanoate, t-butylperoxyisobutyrate, t-butylperoxymaleic acid, t-butylperoxylaurate, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxyisopropyl monocarbonate, t-butylperoxy-2-ethylhexyl monocarbonate, 2,5-dimethyl-2,5-bis(benzoylperoxy)hexane, t-butylperoxyacetate, t-hexylperoxybenzoate, t-butylperoxyethylhexanoate, Organic peroxides such as 2,2'-azobis(N-butyl-2-methylpropionamide), 2,2'-azobis(N-cyclohexyl-2-methylpropionamide), 2,2'-azobis[N-(2-methylpropyl)-2-methylpropionamide], 2,2'-azobis[N-(2-methylethyl)-2- ... 2,2'-azobis(N-hexyl-2-methylpropionamide), 2,2'-azobis(N-propyl-2-methylpropionamide), 2,2'-azobis(N-ethyl-2-methylpropionamide), 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}, 2,Examples of the azo compounds include 2'-azobis[N-(2-propenyl)-2-methylpropionamide] and dimethyl-1,1'-azobis(1-cyclohexanecarboxylate). Among these, from the viewpoint of storage stability, organic peroxides are preferred, and dicumyl peroxide, t-butylcumyl peroxide, and di-t-butyl peroxide are more preferred.

[0048] Examples of the thermal anionic polymerization initiator include imidazole compounds such as 2-methylimidazole, 2-ethylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, 2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, and 2,4-diamino-6-[2-(2-methyl-1-imidazolyl)ethyl]-1,3,5-triazine; amine compounds such as triethylamine, triethylenediamine, 2-(dimethylaminomethyl)phenol, 1,8-diaza-bicyclo[5.4.0]undecene-7, tris(dimethylaminomethyl)phenol, and benzyldimethylamine; Examples of organic phosphorus compounds include phenylphosphine, tributylphosphine, trioctylphosphine, tetrabutylphosphonium hexafluorophosphate, tetrabutylphosphonium tetraphenylborate, tetrabutylphosphonium acetate, tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium bromide, tetrabutylphosphonium bromide, tetrabutylphosphonium laurate, tetraphenylphosphonium hydrogen phthalate, bis(tetraphenylphosphonium)dihydrogenpyromellitate, and bis(tetrabutylphosphonium)dihydrogenpyromellitate. Among these, imidazole compounds and organic phosphorus compounds are preferred, and 1-cyanoethyl-2-ethyl-4-methylimidazole, 2,4-diamino-6-[2-(2-methyl-1-imidazolyl)ethyl]-1,3,5-triazine, triphenylphosphine, tetrabutylphosphonium laurate, tetraphenylphosphonium hydrogen phthalate, bis(tetraphenylphosphonium) dihydrogen pyromellitate, and bis(tetrabutylphosphonium) dihydrogen pyromellitate are more preferred.

[0049] Examples of the photopolymerization initiator include benzoyl compounds (or phenyl ketone compounds) such as benzophenone, particularly benzoyl compounds (or phenyl ketone compounds) having a hydroxy group on the carbon atom at the α-position of the carbonyl group, such as 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, and 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one; 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, and 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one. -dimethylamino-2-(4-methyl-benzyl)-1-(4-morpholin-4-yl-phenyl)-butan-1-one and other α-alkylaminophenone compounds; acylphosphine oxide compounds such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bisacylmonoorganophosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide; benzoin ether compounds such as isobutylbenzoin ether; ketal compounds such as acetophenone diethyl ketal; thioxanthone compounds; and acetophenone compounds. In particular, since the radiation generated from UV-LEDs has a single wavelength, when using UV-LEDs as a light source, it is effective to use a photopolymerization initiator that is an α-alkylaminophenone compound or an acylphosphine oxide compound that has an absorption spectrum peak in the 340 to 400 nm region.

[0050] These curing catalysts may be used alone or in combination of two or more. The amount of component (c) is not particularly limited, but is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, and even more preferably 0.3 to 3 parts by mass, per 100 parts by mass of component (a) in the composition of the present invention. Within this range, the resin composition can be sufficiently cured without adversely affecting the physical properties of the resin composition.

[0051] The dielectric loss tangent at 10 GHz of the cured product of the present invention is preferably 0.01 or less, more preferably 0.007 or less, and further preferably 0.0001 to 0.005.

[0052] [Other ingredients] [Adhesion promoter] The resin composition of the present invention may contain an adhesion imparting agent as necessary to impart adhesiveness or tackiness (pressure-sensitive adhesiveness). Examples of adhesion imparting agents include acrylic resins, urethane resins, phenolic resins, terpene resins, silane coupling agents, etc. Among them, acrylic resins and silane coupling agents are preferred for imparting adhesiveness, and terpene resins are preferred for imparting tackiness (pressure-sensitive adhesiveness).

[0053] The acrylic resin is not particularly limited, and examples thereof include lauryl acrylate, stearyl acrylate, isostearyl acrylate, phenoxyethyl acrylate, phenoxydiethylene glycol acrylate, tetrahydrofurfuryl acrylate, isobornyl acrylate, 2-acryloyloxyethyl phthalate, 2-acryloyloxyethyl acid phosphate, polyethylene glycol diacrylate, dimethylol tricyclodecane diacrylate, trimethylolpropane triacrylate, dipentaerythritol hexaacrylate, and the like. Examples of suitable methacrylates include tetrahydrofurfuryl methacrylate, dioxane glycol diacrylate, 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene diacrylate, lauryl methacrylate, phenoxyethyl methacrylate, phenoxydiethylene glycol methacrylate, tetrahydrofurfuryl methacrylate, isobornyl methacrylate, 2-methacryloyloxyethyl phthalate, 2-methacryloyloxyethyl acid phosphate, polyethylene glycol dimethacrylate, and dimethylol tricyclodecane dimethacrylate.

[0054] The terpene resin is not particularly limited, and examples thereof include homopolymers of terpenes such as monoterpenes such as α-pinene, β-pinene, dipentene, and limonene, sesquiterpenes such as cedrene and funnelcene, and diterpenes such as abietic acid, aromatic modified terpene resins which are copolymers of aromatic vinyl compounds such as styrene and α-methylstyrene with the above-mentioned terpenes, and terpene phenol resins which are copolymers of phenols such as phenol, cresol, hydroquinone, naphthol, and bisphenol A with the above-mentioned terpenes, etc. In addition, hydrogenated terpene resins obtained by hydrogenating these terpene resins can also be used.

[0055] The silane coupling agent is not particularly limited, and examples thereof include silane coupling agents such as n-propyltrimethoxysilane, n-propyltriethoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, 2-[methoxy(polyethyleneoxy)propyl]-trimethoxysilane, methoxytri(ethyleneoxy)propyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, and 3-isocyanatopropyltrimethoxysilane.

[0056] The content of the adhesion promoter is not particularly limited, but is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 1 to 5 parts by mass, relative to 100 parts by mass of component (a). Within this range, the adhesive strength or cohesive strength of the resin composition can be further improved without changing the mechanical properties of the resin composition.

[0057] [Antioxidants] The antioxidant is not particularly limited, and examples thereof include n-octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, n-octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)acetate, neododecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, dodecyl-β-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, ethyl Octadecyl-α-(4-hydroxy-3,5-di-t-butylphenyl)isobutyrate, Octadecyl-α-(4-hydroxy-3,5-di-t-butylphenyl)isobutyrate, Octadecyl-α-(4-hydroxy-3,5-di-t-butyl-4-hydroxyphenyl)propionate, 2-(n-octylthio)ethyl-3,5-di-t-butyl-4-hydroxyphenylacetate, 2-(n-octadecylthio)ethyl-3, 5-di-t-butyl-4-hydroxyphenyl acetate, 2-(n-octadecylthio)ethyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 2-(2-stearoyloxyethylthio)ethyl-7-(3-methyl-5-t-butyl-4-hydroxyphenyl)heptanoate, 2-hydroxyethyl-7-(3-methyl-5-t-butyl-4-hydroxyphenyl)propionate, pentaethyl Phenolic antioxidants such as rhythritol tetrakis [3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]; sulfur-based antioxidants such as dilauryl-3,3'-thiodipropionate, dimyristyl-3,3'-thiodipropionate, distearyl-3,3'-thiodipropionate, ditridecyl-3,3'-thiodipropionate, and pentaerythrityl tetrakis (3-laurylthiopropionate);Examples of phosphorus-based antioxidants include tridecyl phosphite, triphenyl phosphite, tris(2,4-di-t-butylphenyl)phosphite, 2-ethylhexyl diphenyl phosphite, diphenyl tridecyl phosphite, 2,2-methylene bis(4,6-di-t-butylphenyl)octyl phosphite, distearyl pentaerythritol diphosphite, bis(2,6-di-t-butyl-4-methylphenyl)pentaerythritol diphosphite, and 2-[[2,4,8,10-tetrakis(1,1-dimethylethyl)dibenzo[d,f][1,3,2]dioxaphosphepin-6-yl]oxy]-N,N-bis[2-[[2,4,8,10-tetrakis(1,1-dimethylethyl)dibenzo[d,f][1,3,2]dioxaphosphepin-6-yl]oxy]-ethyl]ethanamine.

[0058] The content of the antioxidant is not particularly limited, but is preferably 0.00001 to 5 parts by mass, more preferably 0.0001 to 4 parts by mass, and even more preferably 0.001 to 3 parts by mass, relative to 100 parts by mass of component (a). If it is within this range, oxidation of the resin composition can be prevented without changing the mechanical properties of the resin composition.

[0059] [Flame retardant] The flame retardant is not particularly limited, and examples thereof include phosphorus-based flame retardants, metal hydrates, halogen-based flame retardants, guanidine-based flame retardants, etc. Examples of phosphorus-based flame retardants include red phosphorus, ammonium phosphates such as monoammonium phosphate, diammonium phosphate, triammonium phosphate, and ammonium polyphosphate, inorganic nitrogen-containing phosphorus compounds such as guanidine phosphate and phosphoric acid amide, phosphoric acid, phosphine oxide, triphenyl phosphate, tricresyl phosphate, trixylenyl phosphate, cresyl diphenyl phosphate, cresyl di-2,6-xylenyl phosphate, resorcinol bis(diphenyl phosphate), 1,3-phenylene bis(di-2,6-xylenyl phosphate), bisphenol A-bis(diphenyl phosphate), 1,3-phenylene bis( Examples of suitable phosphazene compounds include phosphazene compounds such as diphenyl phosphate, divinyl phenylphosphonate, diallyl phenylphosphonate, bis(1-butenyl) phenylphosphonate, phenyl diphenylphosphinate, methyl diphenylphosphinate, bis(2-allylphenoxy)phosphazene, and dicresylphosphazene, as well as melamine phosphate, melamine pyrophosphate, melamine polyphosphate, melam polyphosphate, melem polyphosphate, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide. Examples of suitable metal hydrates include aluminum hydroxide hydrate and magnesium hydroxide hydrate. Examples of halogen-based flame retardants include hexabromobenzene, pentabromotoluene, ethylene bis(pentabromophenyl), ethylene bistetrabromophthalimide, 1,2-dibromo-4-(1,2-dibromoethyl)cyclohexane, tetrabromocyclooctane, hexabromocyclododecane, bis(tribromophenoxy)ethane, brominated polyphenylene ether, brominated polystyrene, 2,4,6-tris(tribromophenoxy)-1,3,5-triazine, etc. Examples of guanidine-based flame retardants include guanidine sulfamate, guanidine phosphate, etc.

[0060] The content of the flame retardant is not particularly limited, but is preferably 0.01 to 20 parts by mass, more preferably 0.05 to 10 parts by mass, and even more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of component (a). Within this range, flame retardancy can be imparted to the resin composition without changing the mechanical properties of the resin composition.

[0061] [Inorganic filler] The inorganic filler is not particularly limited, and examples thereof include metal oxides such as silica, titanium dioxide, yttrium oxide, aluminum oxide, magnesium oxide, zinc oxide, and beryllium oxide; metal nitrides such as boron nitride, aluminum nitride, and silicon nitride; carbon-containing particles such as silicon carbide, diamond, and graphene; hollow particles such as silica balloons (hollow silica), carbon balloons, alumina balloons, and aluminosilicate balloons; metal elements such as gold, silver, copper, palladium, aluminum, nickel, iron, cobalt, titanium, manganese, zinc, tungsten, platinum, lead, and tin; alloys such as solder, steel, and stainless steel; magnetic metal alloys such as stainless steel, Fe-Cr-Al-Si alloy, Fe-Si-Al alloy, Fe-Ni alloy, Fe-Cu-Si alloy, Fe-Si alloy, Fe-Si-B(-Cu-Nb) alloy, Fe-Si-Cr-Ni alloy, Fe-Si-Cr alloy, and Fe-Si-Al-Ni-Cr alloy; hematite (Fe2O3), magnetite (Fe 3 O 4 ferrites such as Mn-Zn ferrite, Ni-Zn ferrite, Mg-Mn ferrite, Zr-Mn ferrite, Ti-Mn ferrite, Mn-Zn-Cu ferrite, barium ferrite, strontium ferrite, etc. These may be used alone or in combination of two or more.

[0062] By adding metal oxides, metal nitrides, and carbon-containing particles, the linear expansion coefficient of the cured resin composition can be reduced and the thermal conductivity can be increased; by adding hollow particles, the relative dielectric constant, dielectric tangent, density, etc. of the cured resin composition can be reduced; by adding metals and alloys, the electrical conductivity, thermal conductivity, etc. of the cured resin composition can be increased; and by adding ferrites, the cured resin composition can be endowed with electromagnetic wave absorption ability. The shape of the inorganic filler is not particularly limited, and examples thereof include spherical, scaly, flake-like, needle-like, rod-like, and elliptical shapes. Among these, spherical, scaly, flake-like, elliptical, and rod-like shapes are preferred, and spherical, scaly, flake-like, and elliptical shapes are more preferred.

[0063] The primary particle size of the inorganic filler is not particularly limited, but is preferably 0.05 to 500 μm, more preferably 0.1 to 300 μm, and even more preferably 1 to 100 μm, as a median diameter measured by a laser diffraction particle size distribution measuring device. If it is within this range, it is easy to uniformly disperse the inorganic particles in the resin composition, and the inorganic particles do not settle, separate, or become unevenly distributed over time, which is preferable.

[0064] The amount of the inorganic filler is not particularly limited, but is preferably 5 to 3,000 parts by mass, more preferably 10 to 2,500 parts by mass, and even more preferably 50 to 2,000 parts by mass, relative to 100 parts by mass of component (a) in the composition of the present invention. Within this range, the function of the inorganic particles can be fully exhibited while maintaining the strength of the resin composition.

[0065] [Organic filler] The organic filler is not particularly limited, and examples thereof include thermoplastic resin particles such as acrylic-butadiene copolymer, styrene-butadiene copolymer, acrylonitrile-styrene-butadiene copolymer, acrylic block copolymer, carbon fiber, cellulose fiber, silicone powder, acrylic powder, polytetrafluoroethylene powder, polyethylene powder, polypropylene powder, etc. These may be used alone or in combination of two or more.

[0066] The shape of the organic filler is not particularly limited, and examples thereof include spherical, fibrous, flake-like, needle-like, rod-like, and elliptical shapes. Among these, spherical, fibrous, flake-like, elliptical, and rod-like shapes are preferred, and spherical, fibrous, flake-like, and elliptical shapes are more preferred.

[0067] The primary particle size of the organic filler is not particularly limited, but is preferably 0.05 to 500 μm, more preferably 0.1 to 300 μm, and even more preferably 1 to 100 μm, as a median diameter measured by a laser diffraction particle size distribution measuring device. If it is within this range, it is preferable because it is easy to uniformly disperse the organic particles in the resin composition and the organic particles do not settle, separate, or become unevenly distributed over time.

[0068] The amount of the organic filler is not particularly limited, but is preferably 1 to 400 parts by mass, more preferably 5 to 200 parts by mass, and even more preferably 10 to 100 parts by mass, per 100 parts by mass of component (a) in the composition of the present invention. If the amount is within this range, it is possible to increase the strength of the resin composition.

[0069] [Manufacturing method] The method for producing the resin composition of the present invention includes, for example, a method of mixing the components (a) to (c) and other additives added as necessary using a planetary mixer (manufactured by Inoue Seisakusho Co., Ltd.) or a mixer THINKY CONDITIONING MIXER (manufactured by Thinky Corporation), and preferably a method of further adding and mixing an organic solvent (e.g., cyclopentanone, cyclopentanone, cyclohexanone, mesitylene, anisole, dibutyl ether, diphenyl ether, 1,4-dioxane, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone, etc.). By adding an organic solvent, the viscosity of the resin composition can be reduced and more uniformly mixed. The organic solvent is distilled off under reduced pressure after mixing to obtain a resin composition, but when used as a liquid adhesive or prepreg, it may be used as it is without distilling off, or may be adjusted to a desired concentration before use.

[0070] [Liquid adhesive] The cyclic imide resin composition of the present invention can also be used as a liquid adhesive by dissolving it in the above-mentioned organic solvent, applying or spraying it onto an adherend, and drying by heating. The application or spraying method is not particularly limited, and a dispenser or a spray can be used. The heat drying method is not particularly limited and may be selected according to the volatility of the solvent used. For example, the coating can be dried by heating at a temperature of 40 to 120° C. for 1 to 10 minutes.

[0071] [film] The cyclic imide resin composition of the present invention can also be used as a film by dissolving it in the above-mentioned organic solvent, coating it into a thin film on a film having releasability, and drying it by heating.

[0072] The film having releasability is optimized depending on the type of cyclic imide resin composition, and examples thereof include fluororesin-coated PET (polyethylene terephthalate) films, silicone resin-coated PET films, fluororesin films such as PTFE (polytetrafluoroethylene), ETFE (poly(ethylene-tetrafluoroethylene)), and CTFE (polychlorotrifluoroethylene), etc. These releasable films make it easier to handle the film containing the cyclic imide resin composition of the present invention (hereinafter also referred to as "cyclic imide resin film" or simply "film"), and can prevent adhesion of foreign matter such as dust.

[0073] The thickness of the cyclic imide resin film is not particularly limited, but is preferably 1 μm to 2,000 μm, more preferably 1 μm to 500 μm, and even more preferably 10 μm to 300 μm. If it is thinner than 1 μm, it is difficult to attach it to a substrate, and if it is thicker than 2,000 μm, it is difficult to maintain the flexibility of the film. In addition, when the film contains an inorganic filler or an organic filler, the thickness of the film is preferably at least twice the particle size of the filler, more preferably at least three times, and even more preferably at least five times and no more than 1,000 times. This range is preferable because it is difficult for the inorganic particles to cause unevenness in the film.

[0074] The cyclic imide resin film can be used, for example, by removing a releasable resin film, sandwiching the cyclic imide resin film between adherends, and then heating and pressing to cure the film. The heating temperature is preferably 100°C to 300°C for 1 minute to 4 hours, more preferably 120°C to 250°C for 2 minutes to 3 hours, and even more preferably 150°C to 200°C for 3 minutes to 2 hours. The pressure during pressing is preferably 0.01 MPa to 100 MPa, more preferably 0.05 MPa to 80 MPa, and even more preferably 0.1 MPa to 50 MPa.

[0075] The film of the present invention may be semi-cured (B-staged) in advance by heat or light. There are no particular limitations on the method for B-staging. For example, after coating the cyclic imide resin composition, the film may be heated at a temperature of 80 to 200° C. for 1 to 30 minutes, or irradiated with light of 200 to 400 nm at 10 to 3,000 mJ / cm. 2 By irradiating the area, the B-stage can be achieved.

[0076] [Prepreg] The cyclic imide resin composition of the present invention can also be used as a prepreg by dissolving it in the above-mentioned organic solvent, impregnating a fiber substrate, and drying by heating. The fiber substrate may be any known fiber substrate used in laminates. Examples include inorganic fibers such as E glass, S glass, T glass, NE glass, and Q glass (quartz glass); and organic fibers such as polyethylene, polyester, polyamide, and polytetrafluoroethylene. These may be used alone or in combination of two or more. Among these, inorganic fibers are preferred from the viewpoint of dielectric properties, and T glass, NE glass, and Q glass are more preferred. The thickness of the fiber base material is not particularly limited, but is preferably 5 to 500 μm, more preferably 10 to 100 μm, and even more preferably 20 to 80 μm. Within this range, a prepreg with excellent flexibility, low warpage, and high strength can be obtained. These fiber substrates may be surface-treated by heating or with a silane coupling agent in order to improve the dielectric properties and affinity to resins. The content of the cyclic imide resin composition in the prepreg is not particularly limited, but is preferably 20 to 90% by volume, more preferably 30 to 80% by volume, and even more preferably 40 to 70% by volume. Within this range, the adhesive strength to the conductor can be increased while maintaining the dielectric properties and low warpage. The thickness of the prepreg of the present invention is not particularly limited, but is preferably 10 to 500 μm, more preferably 25 to 300 μm, and even more preferably 40 to 200 μm. If it is within this range, a copper-clad laminate can be satisfactorily produced. The prepreg of the present invention may be semi-cured (B-staged) in advance by heating. There are no particular limitations on the method for B-staging, but for example, the cyclic imide resin composition of the present invention is dissolved in a solvent, impregnated into a fiber substrate, dried, and then heated at a temperature of 80 to 200°C for 1 to 30 minutes to achieve B-stage.

[0077] [Copper-clad laminate] The prepreg of the present invention may be used as a copper-clad laminate by overlapping copper foil, pressing, and heat curing. There are no particular limitations on the method for producing a copper-clad laminate, but it can be produced, for example, by using 1 to 20 sheets, preferably 2 to 10 sheets, of the prepreg, placing copper foil on one or both sides, pressing, and heat-curing. The thickness of the copper foil is not particularly limited, but is preferably 3 to 70 μm, more preferably 10 to 50 μm, and even more preferably 15 to 40 μm. Within this range, a multi-layer copper-clad laminate that maintains high reliability can be formed. The molding conditions for the copper-clad laminate are not particularly limited, but for example, molding can be performed using a multi-stage press, a multi-stage vacuum press, a continuous molding machine, an autoclave molding machine, etc., at a temperature of 100 to 400°C, a pressure of 1 to 100 MPa, and a heating time of 0.1 to 4 hours. Also, the prepreg of the present invention, copper foil, and an inner layer wiring board can be combined and molded to form a copper-clad laminate.

[0078] [Printed wiring board] The copper-clad laminate of the present invention may be subjected to circuit processing and used as a printed wiring board. The method for circuit processing is not particularly limited, but examples thereof include circuit formation processing methods such as hole drilling, metal plating, and etching of metal foil. Furthermore, a printed wiring board may be produced by a build-up method in which the resin composition or prepreg of the present invention and copper foil are laminated in that order. EXAMPLES

[0079] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0080] The molecular weight of component (a) shown in the following examples is the weight average molecular weight (Mw) measured by gel permeation chromatography (GPC) using polystyrene as the standard substance. The measurement conditions are as follows: [GPC measurement conditions] Developing solvent: Tetrahydrofuran Flow rate: 0.6mL / min Column: TSK Guardcolumn SuperH-L TSKgel SuperH4000(6.0mmI.D.×15cm×1) TSKgel SuperH3000(6.0mmI.D.×15cm×1) TSKgel SuperH2000(6.0mmI.D.×15cm×2) (All manufactured by Tosoh Corporation) Column temperature: 40℃ Sample injection volume: 20 μL (sample concentration: 0.5% by mass in tetrahydrofuran solution) Detector: Differential refractometer (RI)

[0081] [Examples 1 to 20, Comparative Examples 1 to 6] (a) Cyclic imide compounds (a-1) Maleimide compound 253 g (1.003 mol) of 3,3'-diethyl-4,4'-diaminodiphenylmethane (trade name: Kayahard AA (manufactured by Nippon Kayaku Co., Ltd.)) and 520 g (1.0 mol) of 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride were added to 500 g of anisole, and the mixture was stirred at room temperature for 5 hours and further stirred at 120°C for 3 hours. 19 g (0.2 mol) of maleic anhydride was added to the resulting solution, and the mixture was stirred at 150°C for 1 hour. Thereafter, the solvent and unreacted maleic anhydride were distilled off under reduced pressure to obtain maleimide (a-1) represented by the following formula (weight average molecular weight 180,000). [ka]

[0082] (a-2) Maleimide compounds 327g (1.05mol) of 3,3',5,5'-tetraethyl-4,4'-diaminodiphenylmethane and 310g (1.0mol) of 4,4'-oxydiphthalic anhydride were added to 350g of anisole, and the mixture was stirred at room temperature for 3 hours, and further stirred at 120°C for 3 hours. 19g (0.2mol) of maleic anhydride was added to the obtained solution, and the mixture was stirred at 150°C for 1 hour. Thereafter, the solvent and unreacted maleic anhydride were distilled off under reduced pressure to obtain maleimide (a-2) represented by the following formula (weight average molecular weight 58,000). [ka]

[0083] (a-3) Maleimide compounds 220g (1.1mol) of 4,4'-diaminodiphenyl ether and 310g (1.0mol) of 4,4'-oxydiphthalic anhydride were added to 300g of anisole, and the mixture was stirred at room temperature for 5 hours and further stirred at 120°C for 3 hours. 19g (0.2mol) of maleic anhydride was added to the obtained solution, and the mixture was stirred at 150°C for 1 hour. Thereafter, the solvent and unreacted maleic anhydride were distilled off under reduced pressure to obtain maleimide (a-3) represented by the following formula (weight average molecular weight 5,000). [ka]

[0084] (a-4) Maleimide compounds 431 g (1.05 mol) of 2,2-bis(4-(4-aminophenoxy)phenyl)propane and 520 g (1.0 mol) of 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride were added to 500 g of anisole, and the mixture was stirred at room temperature for 5 hours and further stirred at 120°C for 3 hours. 19 g (0.2 mol) of maleic anhydride was added to the obtained solution, and the mixture was stirred at 150°C for 1 hour. Thereafter, the solvent and unreacted maleic anhydride were distilled off under reduced pressure to obtain maleimide (a-4) represented by the following formula (weight average molecular weight 45,000). [ka]

[0085] (a-5) Maleimide compounds 171g (0.55mol) of 3,3',5,5'-tetraethyl-4,4'-diaminodiphenylmethane, 305g (0.55mol) of Priamine 1075 (manufactured by Croda Japan Co., Ltd.) and 310g (1.0mol) of 4,4'-oxydiphthalic anhydride were added to 400g of anisole, and the mixture was stirred at room temperature for 5 hours, and further stirred at 120°C for 3 hours. 19g (0.2mol) of maleic anhydride was added to the obtained solution, and the mixture was stirred at 150°C for 1 hour. Thereafter, the solvent and unreacted maleic anhydride were distilled off under reduced pressure to obtain (a-5) maleimide represented by the following formula (weight average molecular weight 26,000). [ka]

[0086] (a-6) Maleimide compounds Maleimide compound represented by the following formula (product name: BMI-3000, manufactured by Designer Molecules Inc.) (weight average molecular weight: 10,000) [ka]

[0087] (a-7) Citraconimide compounds 277g (1.1mol) of 3,3'-diethyl-4,4'-diaminodiphenylmethane (trade name: Kayahard AA (manufactured by Nippon Kayaku Co., Ltd.)) and 520g (1.0mol) of 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride were added to 350g of anisole, and the mixture was stirred at room temperature for 3 hours, and further stirred at 120°C for 3 hours. 26g (0.2mol) of citraconic anhydride was added to the obtained solution, and the mixture was stirred at 150°C for 1 hour. Thereafter, the solvent and unreacted citraconic anhydride were distilled off under reduced pressure to obtain citraconic imide (a-7) represented by the following formula (weight average molecular weight 41,000). [ka]

[0088] (b1) A compound having at least two groups selected from an alkenyl group, a maleimide group, a (meth)acrylic group, an epoxy group, and a cyanate group in one molecule, and having a dipole moment calculated by Gaussian 16 of less than 1.2 DeBye. (b1-1) Alkenyl compounds Alkenyl compound represented by the following formula (trade name: Taiku, manufactured by Mitsubishi Chemical Corporation) (dipole moment 0.225 DeBye) (molecular weight 249) [ka]

[0089] (b1-2) Alkenyl compounds Octavinyl octasilsesquioxane (dipole moment 0.937 DeBye) (molecular weight 633) represented by the following formula [ka]

[0090] (b1-3) Maleimide compounds Maleimide compound represented by the following formula (trade name: BMI-TMH, manufactured by Daiwa Kasei Kogyo Co., Ltd.) (dipole moment 0.467 DeBye) (molecular weight 318) [ka]

[0091] (b1-4) Maleimide compounds Maleimide compound represented by the following formula (trade name: BMI-689, manufactured by Designer Molecules Inc.) (dipole moment 1.073 DeBye) (molecular weight 695) [ka]

[0092] (b1-5) Alkenyl compounds 100g of 2,6-dimethylphenol and 3g of copper oxide were added to 500g of toluene, and the mixture was stirred at 50°C for 5 hours while bubbling oxygen gas. Then, 3g of ethylenediamine was added and stirred at room temperature for 1 hour, and the reaction solution was reprecipitated in methanol to obtain a phenylene ether oligomer. The obtained oligomer was dissolved in 400g of toluene, and 20g of 50% aqueous sodium hydroxide solution and 380g of p-chloromethylstyrene were added, and the mixture was stirred at 60°C for 1 hour. Then, the solvent was distilled off under reduced pressure, and the mixture was filtered through alumina to obtain an alkenyl compound (b1-5) represented by the following formula. (Dipole moment 1.073 DeBye) (Molecular weight 970) [ka]

[0093] (b1-6) Acrylic compounds 100g of 2,6-dimethylphenol and 3g of copper oxide were added to 500g of toluene, and the mixture was stirred at 50°C for 5 hours while bubbling oxygen gas. Then, 3g of ethylenediamine was added and stirred at room temperature for 1 hour, and the reaction solution was reprecipitated in methanol to obtain a phenylene ether oligomer. The obtained oligomer was dissolved in 400g of toluene, and 20g of 50% aqueous sodium hydroxide solution and 200g of acryloyl chloride were added, and the mixture was stirred at 5°C for 1 hour. Then, the solvent was distilled off under reduced pressure, and the mixture was filtered through alumina to obtain the acrylic compound (b1-6) represented by the following formula. (Dipole moment 1.061 DeBye) (Molecular weight 850) [ka]

[0094] (b1-7) Epoxy compounds 100g of 2,6-dimethylphenol and 3g of copper oxide were added to 500g of toluene, and the mixture was stirred at 50°C for 5 hours while bubbling oxygen gas. Then, 3g of ethylenediamine was added and stirred at room temperature for 1 hour, and the reaction solution was reprecipitated in methanol to obtain a phenylene ether oligomer. The obtained oligomer was dissolved in 400g of toluene, and 20g of 50% aqueous sodium hydroxide solution and 150g of epichlorohydrin were added, and the mixture was stirred at 60°C for 2 hours. Then, the solvent was distilled off under reduced pressure, and the mixture was filtered through alumina to obtain an epoxy compound (b1-7) represented by the following formula. (Dipole moment 1.096 DeBye) (Molecular weight 850) [ka]

[0095] (b2) A compound having at least two groups selected from an alkenyl group, a maleimide group, a (meth)acrylic group, an epoxy group, and a cyanate group in one molecule, and having a dipole moment calculated by Gaussian 16 of 1.2 DeBye or more.

[0096] (b2-1) Maleimide compounds 4,4-Bismaleimidodiphenylmethane (dipole moment 1.387 DeBye) (molecular weight 358) represented by the following formula [ka]

[0097] (b2-2) Epoxy compounds Epoxy compound represented by the following formula (trade name: NC-3000, manufactured by Nippon Kayaku Co., Ltd.) (dipole moment 1.571 DeBye) (molecular weight 810) [ka]

[0098] (b2-3) Maleimide compounds Maleimide compound represented by the following formula (trade name: BMI-2300, manufactured by Daiwa Kasei Kogyo Co., Ltd.) (dipole moment 1.724 DeBye) (molecular weight 400) [ka]

[0099] (b2-4) Maleimide compounds Maleimide compound represented by the following formula (trade name: BMI-4000, manufactured by Daiwa Kasei Kogyo Co., Ltd.) (dipole moment 1.241 DeBye) (molecular weight 570) [ka]

[0100] (c) Curing catalyst (c-1) Dicumyl peroxide (c-2) 2,4-diamino-6-[2-(2-methyl-1-imidazolyl)ethyl]-1,3,5-triazine (trade name: "2MZ-A" (manufactured by Shikoku Chemical Industry Co., Ltd.)) (c-3) Triphenylphosphine

[0101] (d) Inorganic fillers (d-1) Silica "SFP-130MC" (median primary particle size: 0.6 μm) (manufactured by Denka Co., Ltd.) (d-2) Alumina "AO-41R" (median primary particle size: 6 μm) (manufactured by Admatechs Co., Ltd.)

[0102] (e) Organic fillers (e-1) Silicone powder "KMP-600" (median primary particle size: 5 μm) (Shin-Etsu Chemical Co., Ltd.)

[0103] (f) Adhesion promoter (f-1) Silane coupling agent (3-glycidoxypropyltrimethoxysilane, product name "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd.) (f-2) Silane coupling agent (N-phenyl-3-aminopropyltrimethoxysilane, product name "KBM-573", manufactured by Shin-Etsu Chemical Co., Ltd.)

[0104] (g) Antioxidants (g-1) Pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (trade name: Adeka STAB AO-60, manufactured by ADEKA Corporation)

[0105] (h) Flame retardants (h-1) Guanidine phosphate (product name: Apinon-303, manufactured by Sanwa Chemical Co., Ltd.)

[0106] [Method for preparing resin composition] For Examples 1 to 20 and Comparative Examples 1 to 6, in addition to the formulations (parts by mass) shown in Tables 1 to 3, 100 parts by mass of cyclopentanone was added and mixed for a total of 100 parts by mass of each component, and the mixture was kneaded at 80° C. for 30 minutes using a planetary mixer (Inoue Seisakusho Co., Ltd.), and then cooled to 25° C. The resulting solution was transferred to a flask, and the solvent was distilled off under reduced pressure to prepare a resin composition.

[0107] [Tensile strength and elongation at break of cured product] The uncured resin compositions obtained in Examples 1 to 20 and Comparative Examples 1 to 6 were press-cured at 200°C for 1 hour to prepare test samples (cured products) of 150 mm x 200 mm x 50 μm thick. In accordance with JIS K 6251:2010, the tensile strength (MPa) and elongation at break (%) of the test samples (cured products) were measured using an EZ TEST (EZ-L, manufactured by Shimadzu Corporation) under conditions of a test speed of 500 mm / min, a gripper distance of 80 mm, and a gauge length of 40 mm. The results are shown in Tables 1 to 3.

[0108] [Dielectric constant and dielectric loss tangent] The prepared uncured resin composition was sandwiched between a mold frame of 30 mm x 40 mm x 100 μm thickness and press cured at 200° C. for 1 hour to prepare a test sample (cured product). A network analyzer (E5063-2D5 manufactured by Keysight) and a strip line (manufactured by Keycom Co., Ltd.) were connected to the prepared test sample (cured product) to measure the relative dielectric constant and dielectric loss tangent at a frequency of 10 GHz. The results are shown in Tables 1 to 3.

[0109] [Peel Strength] The uncured resin composition prepared by the above method was coated in a film shape to a thickness of 25 μm, and a SUS plate, the film, and a copper foil having a thickness of 18 μm (product name: TQ-M4-VSP, manufactured by Mitsui Metals Co., Ltd.) were stacked in this order and pressed, and the composition was cured by heating at 200°C for 1 hour. In accordance with the standard JIS-C-6481:1996 for testing copper-clad laminates for printed wiring boards, the force (kN / m) when peeling the copper foil from the resin film at a speed of 50 mm / min in a 90° direction with a width of 10 mm was measured using a Tensilon tester (manufactured by Toyo Seiki Seisakusho Co., Ltd., product name: Strograph VE-1D). The results are shown in Tables 1 to 3.

[0110] [Glass transition temperature] The storage modulus (MPa) of the test sample (cured product) prepared as described in the above section [Tensile strength and elongation at break of the cured product] was measured in the range of 0°C to 300°C using a DMA Q800 (manufactured by TA Instruments Co., Ltd.), and the peak top temperature obtained from a graph plotting the Tan δ values ​​derived from the obtained storage modulus and loss modulus values ​​was taken as the glass transition temperature (Tg). The measurement conditions were a test sample (cured product) of 20 mm x 5 mm x 50 μm thickness, a heating rate of 5°C / min, multi-frequency mode, tensile mode, and amplitude of 15 μm. The results are shown in Tables 1 to 3.

[0111] [Table 1]

[0112] [Table 2]

[0113] [Table 3]

[0114] In Examples 1 to 20, the cured products had low relative dielectric constants and low dielectric tangents, high peel strengths, and high glass transition points. In Comparative Examples 1 and 2, which did not contain component (a) and contained component (b2) a maleimide compound with a molecular weight of less than 2,000, the tensile strength and peel strength of the cured product were low, and the relative dielectric constant and dielectric loss tangent were also high. In Comparative Examples 3 and 4, the component (b1) was not contained, but the component (b2) was contained, and therefore the relative dielectric constant and the dielectric loss tangent were high. In Comparative Examples 5 and 6, the blending amount of the (b2) component was large, and therefore the dielectric tangent was high.

[0115] [Prepreg manufacturing method] 1,000 g of each of the resin compositions prepared in Examples 1, 11, 15, Comparative Examples 3, and 4 was mixed with 1,000 g of cyclopentanone, impregnated into a quartz glass cloth SQX2116AC (thickness 90 μm, manufactured by Shin-Etsu Chemical Co., Ltd.), and heated at 120° C. for 5 minutes to volatilize the cyclopentanone, producing a prepreg. The content (mass%) of the cyclic imide resin composition and the thickness of the prepreg are shown in Table 4.

[0116] [Manufacturing method of copper clad laminate] Ten sheets of the prepreg obtained above and 18 μm thick copper foil (product name: TQ-M4-VSP, manufactured by Mitsui Metals Co., Ltd.) were stacked in order, pressed at 3 MPa, and heated at 200° C. for 1 hour to produce a copper-clad laminate.

[0117] [Printed wiring board manufacturing method] A 30μm-thick dry resist film (NIT430E, Nikko Materials Co., Ltd.) was vacuum laminated at 80℃ for 60 seconds onto the copper-clad laminate obtained above. A mask with a circuit pattern was then contacted, UV was irradiated from above, and the film was developed with an aqueous solution of sodium bicarbonate. The film was then immersed in an etching solution (H-1000A, Sanhayato Co., Ltd.) for etching, and washed with an aqueous solution of sodium hydroxide to produce a printed wiring board with a circuit formed.

[0118] [Transmission loss] Using a network analyzer (Keysight Technologies, part number E5071C), the transmission loss at 40 GHz was measured with the conductor length set to 400 mm, the copper foil thickness set to 18 μm, the line width set to 0.12 mm, the insulation layer thickness set to 0.20 mm, and the characteristic impedance set to 50 Ω. The results are shown in Table 4.

[0119] [Table 4]

[0120] In the examples, a printed wiring board having a small transmission loss value was manufactured. In the comparative example, since the component (b1) was not contained but the component (b2) was contained, the transmission loss value was large.

Claims

1. A cyclic imide resin composition comprising the following components (a), (b) and (c): (a) A cyclic imide compound represented by the following formula (2) having a weight average molecular weight of 2,000 to 1,000,000: 【Chemistry 1】 (In formula (2), A independently represents a tetravalent organic group containing a cyclic structure. B 1 independently represents an alkylene group having 6 to 60 carbon atoms which may contain a heteroatom or a divalent hydrocarbon group derived from a dimer acid skeleton. B 2 independently represents an arylene group having 6 to 30 carbon atoms which may contain a heteroatom. X represents a hydrogen atom or a methyl group. W represents B 1 or B 2 . m 1 represents 0 to 500, and m 2 represents 1 to 500.) (b) a compound having a molecular weight of less than 2,000 and having at least two groups selected from an alkenyl group, a maleimide group, a (meth)acrylic group, an epoxy group, and a cyanate group in each molecule, (b1) A compound having a dipole moment of 1.1 Debye or less as calculated by Gaussian 16. 1 to 50 parts by mass per 100 parts by mass of component (a). (b2) a compound having a dipole moment of 1.2 DeBye or more as calculated by Gaussian 16; 10 parts by mass or less per 100 parts by mass of component (a); (c) Curing catalyst

2. 2. The cyclic imide resin composition according to claim 1, wherein the organic group represented by A in formula (2) is any one of tetravalent organic groups represented by the following structural formulas: 【Chemistry 2】 (The bond not bonded to a substituent in the above structural formula is bonded to the carbonyl carbon that forms a cyclic imide structure in formula (2).)

3. B in formula (2) 1 2. The cyclic imide resin composition according to claim 1, wherein the alkylene group having 6 to 60 carbon atoms and optionally containing a heteroatom is selected from the group represented by the following structural formula and a divalent hydrocarbon group derived from a dimer acid skeleton: 【Chemistry 3】 (R 1 each independently represents a hydrogen atom or a linear or branched alkyl group having 1 to 20 carbon atoms. 1 and p 2 are each a number of 5 or more, and may be the same or different; p 3 and p 4 are each a number of 0 or more and may be the same or different, p 5 is a number from 6 to 60. The bond to which no substituent is bonded in the above structural formula is bonded to the nitrogen atom that forms a cyclic imide structure in formula (2).

4. B in formula (2) 2 2. The cyclic imide resin composition according to claim 1, wherein the arylene group having 6 to 30 carbon atoms and optionally containing a heteroatom, represented by the following structural formula, is any one of the groups represented by the following structural formulas: 【Chemistry 4】 (R 2 are each independently a hydrogen atom, a halogen atom, or an alkyl group having 1 to 6 carbon atoms; R 3 are each independently a hydrogen atom, a halogen atom, a methyl group, or a trifluoromethyl group, and Z is an oxygen atom, a sulfur atom, or a methylene group. The bond to which no substituent is bonded in the above structural formula is bonded to the nitrogen atom that forms a cyclic imide structure in formula (2).

5. The cyclic imide compound of the component (a) is represented by the formula (2) m 1 The cyclic imide resin composition according to claim 1, wherein the cyclic imide compound is a cyclic imide compound having a formula (II) of 0.

6. The cyclic imide resin composition of claim 1, further comprising at least one selected from an inorganic filler, an organic filler, an adhesion promoter, an antioxidant and a flame retardant.

7. A liquid adhesive comprising the cyclic imide resin composition according to any one of claims 1 to 6.

8. A film comprising the cyclic imide resin composition according to any one of claims 1 to 6.

9. A prepreg comprising the cyclic imide resin composition according to any one of claims 1 to 6.

10. A copper-clad laminate comprising the prepreg according to claim 9.

11. A printed wiring board comprising the copper-clad laminate according to claim 10.

Citation Information

Patent Citations

  • Resin composition

    JP2018028044A

  • Flame-retardant resin composition and copper foil with resin

    JP2018044065A

  • Resin composition, prepreg, metal-clad laminate, and printed wiring board

    JP2019001965A

  • Thermosetting resin composition

    JP2020045446A

  • Resin composition

    JP2021011587A